Fetal Growth and Neurobehavioral Outcomes in Childhood - Pinka Chatterji; Dohyung Kim; Kajal Lahiri (Center for Economic Studies and ifo Institute (CESifo), 2014)
Using a sample of sibling pairs from a nationally representative U.S. survey, we examine the effects of the fetal growth rate on a set of neurobehavioral outcomes in childhood measured by parent-reported diagnosed developmental disabilities and behavior problems. Based on models that include mother fixed effects, we find that the fetal growth rate, a marker for the fetal environment, is negatively associated with lifetime diagnosis of developmental delay. We also find that the fetal growth rate is negatively associated with disruptive behaviors among male children. These results suggest that developmental disabilities and problem behaviors may play a role in explaining the well-documented association between birth weight and human capital outcomes measured in adulthood.
Keywords: I12; I20; 330; low birth weight; fetal growth; neurobehavioral outcomes; developmental disabilities; Behavior Problems Index (BPI)